Crossroads of continents : cultures of Siberia and Alaska - Crowell, Aron, 1952-; Fitzhugh, William W., 1943-; National Museum of Natural History (U.S.) (Washington, D.C. : Smithsonian Institution Press, 1988)
An exhibition examining the origins of the peoples of North America.
"Crossroads of continents is also the title of an exhibition organized by the National Museum of Natural History and circulated by the Smithsonian Traveling Exhibition Service (SITES)"--T.p. verso.
Bibliography: p. 354-359.
Keywords: Eskimos -- Alaska -- Exhibitions; Ethnology -- Russia (Federation) -- Siberia -- Exhibitions; Indians of North America -- Alaska -- Exhibitions; Ethnology; Indians of North America -- Alaska; Inuit -- Exhibitions; Siberia (R.S.F.S.R.); Alaska -- Social life and customs -- Exhibitions; Siberia (Russia) -- Social life and customs -- Exhibitions